Deciphering novel TCF4-driven mechanisms underlying a common triplet repeat expansion-mediated disease - Bhattacharyya, Nihar; Chai, Niuzheng; Hafford-Tear, Nathaniel J; Sadan, Amanda N; Szabo, Anita; Zarouchlioti, Christina; Jedlickova, Jana; Leung, Szi Kay; Liao, Tianyi; Dudakova, Lubica; Skalicka, Pavlina; Parekh, Mohit; et al. (PLoS genetics, 2024)
Fuchs endothelial corneal dystrophy (FECD) is an age-related cause of vision loss, and the most common repeat expansion-mediated disease in humans characterised to date. Up to 80% of European FECD cases have been attributed to expansion of a non-coding CTG repeat element (termed CTG18.1) located within the ubiquitously expressed transcription factor encoding gene, TCF4. The non-coding nature of the repeat and the transcriptomic complexity of TCF4 have made it extremely challenging to experimentally decipher the molecular mechanisms underlying this disease. Here we comprehensively describe CTG18.1 expansion-driven molecular components of disease within primary patient-derived corneal endothelial cells (CECs), generated from a large cohort of individuals with CTG18.1-expanded (Exp+) and CTG 18.1-independent (Exp-) FECD. We employ long-read, short-read, and spatial transcriptomic techniques to interrogate expansion-specific transcriptomic biomarkers. Interrogation of long-read sequencing and alternative splicing analysis of short-read transcriptomic data together reveals the global extent of altered splicing occurring within Exp+ FECD, and unique transcripts associated with CTG18.1-expansions. Similarly, differential gene expression analysis highlights the total transcriptomic consequences of Exp+ FECD within CECs. Furthermore, differential exon usage, pathway enrichment and spatial transcriptomics reveal TCF4 isoform ratio skewing solely in Exp+ FECD with potential downstream functional consequences. Lastly, exome data from 134 Exp- FECD cases identified rare (minor allele frequency <0.005) and potentially deleterious (CADD>15) TCF4 variants in 7/134 FECD Exp- cases, suggesting that TCF4 variants independent of CTG18.1 may increase FECD risk. In summary, our study supports the hypothesis that at least two distinct pathogenic mechanisms, RNA toxicity and TCF4 isoform-specific dysregulation, both underpin the pathophysiology of FECD. We anticipate these data will inform and guide the development of translational interventions for this common triplet-repeat mediated disease.
Keywords: Fuchsova endoteliální dystrofie; Transcription Factor 4; transkriptom; Transcriptome; Alternative Splicing; Male; transkripční faktor 4; rohovkový endotel; Endothelial Cells; lidé; Trinucleotide Repeat Expansion; alternativní sestřih; endoteliální buňky; mužské pohlaví; Endothelium, Corneal; Humans; expanze trinukleotidových repetic; Fuchs' Endothelial Dystrophy